Insights into rare diseases from social media surveys - Davies, William (Orphanet J Rare Dis, 2016)
The internet, and social media platforms, are increasingly being used by substantial sectors of the worldwide population. By engaging effectively with online and social media, scientists and clinicians can obtain unprecedented access to relatively large cohorts of individuals with rare diseases, as well as their relatives, carers and professionals involved in their healthcare. Online surveys of these stakeholder groups may provide important new insights into rare conditions and their management relatively quickly and easily, with the possibility of rapid translation into healthcare interventions and policy. Here, I describe our recent positive experience with the online survey approach to a rare disease (X-linked ichthyosis), and review its advantages and limitations.